(untitled) (Agro Productividad, 2025)
Objective: To determine the relationship between the quantity produced of the main agricultural product of each Mexican state and its price. Design/Methodology/Approach: Sixty-two cointegration tests were conducted to examine the relationship between the production levels and the price of the main agricultural product of each state, with the exception of Baja California due to lack of data. Results: Generally, the price does not influence the production of the main agricultural product in the 31 states analyzed over the long term. Only fifteen exceptions were found in the 62 tests conducted, which contradicts the existing literature. This lack of influence could be attributed to the specific characteristics of the crops studied, the available infrastructure, state-specific conditions, or the implementation of government programs. However, as mentioned, there are exceptions. Study Limitations: The States were not characterized in detail. Findings/Conclusions: Overall, there is no significant relationship between the price and the production levels of the main agricultural product of each Mexican state.